Survey of Firearm Storage Practices and Preferences Among Parents and Caregivers of Children - Meredith B. Haag; Catlin H. Dennis; Steven McGaughey; Tess A. Gilbert; Susan DeFrancesco; Adrienne R. Gallardo; Benjamin D. Hoffman; Kathleen F. Carlson (Western Journal of Emergency Medicine)
Introduction: The American College of Emergency Physicians supports community- and hospital-based programs that intervene to prevent firearm-related injury. To this end, the distribution of firearm locks or storage devices in the emergency department (ED) may help achieve this target. To inform secure firearm storage programs for households with children and firearms, we examined firearm storage practices, device preferences, and cost tolerance among parents/caregivers of children. Methods: Between April 2018–November 2019, we conducted and analyzed an in-person survey of 294 caregivers, aged ≥18, with both children and firearms in the home. Surveys assessed reasons for firearm ownership, storage practices and device preferences among five storage-device options, and prices participants were willing to pay for devices. Practices and preferences were examined by participant characteristics. We used logistic regression to estimate odds ratios and 95% confidence intervals for associations of interest. Results: Most participants (73%) reported personal protection as a reason for owning firearms, and nearly 80% owned at least one firearm storage device. Over half (55%) owned cable locks, but only 36% of owners reported regularly using them. Rapid-access devices (electronic and biometric lockboxes) were less commonly owned (26%) but more likely to be regularly used (73%). The most highly rated storage device features were the following: the ability to store the firearm unloaded (87.3%); the ability to store the firearm loaded (79.1%); and device affordability (65%). Most participants (78%) preferred rapid-access devices over other options. Participants were willing to pay more for products that afforded rapid access to the firearm. Participants reported they would pay a median of $100 for a pushbutton rapid-access product ($80 retail), and $150 for a biometric lockbox ($210 retail). Conclusion: Understanding the storage practices and preferences among firearm-owning households with children can help inform ED injury-prevention screening and firearm safety practice implementation. Our results suggest that rapid-access devices may be the most preferable firearm storage devices for distribution by secure storage programs, and costs are likely minimal given parental/caregiver willingness to pay.